Sustainable intensification of small-scale aquaculture production in Myanmar through diversification and better management practices - Wang, Quanli; Rossignoli, Cristiano M.; Dompreh, Eric; Su, Jie; Ali, Syed; Karim, Manjurul; Gasparatos, Alexandros (IOP Publishing, 2023)
Small-scale aquaculture systems can contribute significantly to food and nutritional security, poverty alleviation, and rural development, especially in developing countries. However, the intensification of aquaculture systems often has negative environmental outcomes. The adoption of diversification practices (e.g. polyculture, pond-dike cropping (PDC)) and better management practices (BMPs) has been identified as a possible approach to intensify sustainably small-scale aquaculture production. This study assesses the sustainability outcomes of the adoption of diversification practices and BMPs in small-scale production models. We focus on Myanmar, a developing country characterized by a rapidly expanding small-scale aquaculture sector. We analyze 624 household surveys with small-scale aquaculture producers in central and northern Myanmar. We estimate the effects of diversification practices and BMPs on different sustainability outcomes, namely economic outcomes (i.e. aquaculture yield and benefit-cost ratio), environmental outcomes (i.e. nitrogen and phosphorus use efficiency), and food security outcomes (i.e. fish self-consumption and household dietary diversity) through linear mixed-effects models. Our results reveal that diversified production models (whether integrating or not integrating BMPs) could have significant positive effects on economic and food security outcomes, as well as phosphorus use efficiency, compared to 'unimproved monoculture'. However, such production models do not seem to have any major effect on nitrogen use efficiency. The adoption of BMPs on diversified production models seems to have little (if any) added effect on any of the studied sustainability outcomes, which suggests the need to improve existing BMPs or even develop new BMPs fit for Myanmar's context. These findings have implications about the possible contribution of diversification practices and BMPs for enabling sustainable intensification in small-scale aquaculture settings in Myanmar, and other rural developing contexts.